Mobility Aware RPL (MARPL): Providing Mobility Support for RPL Protocol - Marques, Vinícius de Figueiredo; Kniess, Janine (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2019: Anais do XXXVII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2019)
Low Power and Lossy Network (LLN) is a common type of wireless network in IoT applications. LLN communication patterns usually require an efficient routing protocol. The IPv6 Routing Protocol for Low-Power and Lossy Network (RPL) is considered to be the standard routing protocol for LLNs. However, RPL was developed for static networks and node mobility decreases RPL overall performance. These are the aims of the Mobility Aware RPL (MARPL), presented in this paper. MARPL provides a mobility management based on neighbor variability. MARPL is composed by mechanisms for mobility and link disconnection detection, and DIO and DIS transmission adjustment. Performance evaluation obtained through simulations confirms the effectiveness of MARPL regarding packet delivery rate, overhead and residual energy when compared to RPL, mRPL and D-RPL.